Agentive Movement Verbs in the Study of the Angkola Batak Language - Zainuddin Saragih; Mulyadi (RETORIKA: Jurnal Ilmu Bahasa, 2023)
The Angkola Batak language is a regional language that has 2 types of verbs, namely agentive motion verbs and patient motion verbs. In this study we will discuss agentive motion verbs.The purpose of this study is to determine the categorization of agentive verbs in the Batak Angkola language so that there are no mistakes in the meaning of words. This study used a qualitative approach with data collection techniques using interviews.The results of this study indicate that agentive movement verbs (VGA) are categorized based on eleven components.